2014
DOI: 10.5812/jjm.11802
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Partial Purification and Characterization of an Antimicrobial Compound, Produced by Bacillus atrophaeus

Abstract: Background:Antibiotics are usually assumed as secondary metabolites produced during the idiophase of microbial growth, which can kill or inhibit the growth of other microorganisms. Nowadays, indiscriminate use of antibiotics has resulted in resistant microorganisms. Therefore, screening researches on products with antimicrobial activities are necessary.Objectives:To find new antibiotics to defend against pathogenic microorganisms resistant to common antibiotics, the bacterium isolated from skin of the frog cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
2
7
0
1
Order By: Relevance
“…OA (99% purity or higher) had been isolated from the resin of Scutellariae radix and purified according to the established methods . OA was prepared as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…OA (99% purity or higher) had been isolated from the resin of Scutellariae radix and purified according to the established methods . OA was prepared as described previously .…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Lisboa et al, 2006 has revealed a bacteriocin-like substance produced by Bacillus amyloliquefaciens , which inhibited pathogenic and food-spoilage bacteria ( L. monocytogenes, Bacillus cereus, Serratia marcescens, and Pasteurella haemolytica ). Ebrahimipour et al, 2014 isolated and purified an antimicrobial compound upon extracting the culture of Bacillus atrophaeus by methanol and acetone. Al-Saraireh et al, 2015 extracted the supernatant of Bacillu s isolates from soil and reported its antibacterial activity against Gram positive bacteria, namely B. subtilis , M. luteus and S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…O único patógeno de vertebrados relatado, incluindo seres humanos, é Bacillus antharacis, um parente próximo de B. cereus que causa intoxicação alimentar em cães e seres humanos (BIBERSTEIN et al, 2012b). Algumas espécies deste gênero isoladas de anfíbios já foram testadas e demonstraram atividade antimicrobiana, algo de grande importância visto a atual resistência de microrganismos patogênicos aos antibióticos comuns, fornecendo novas alternativas para formulação de fármacos com essa propriedade (PUKALA et al, 2006;EBRAHIMIPOUR et al, 2014;LOUDON et al, 2014).…”
Section: Que Observaram Emunclassified